ANALISIS TINGKAT PENGUNGKAPAN LAPORAN TAHUNAN SETELAH PENERAPAN PSAK BERBASIS IFRS (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - R u d y - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2014)
The purpose of this studyis to empirically examine the level of disclosure required(mandatory disclosure and voluntary disclosure) annualreport after the implementation of PSAKbased on IFRS.The sample in this study is 17 manufacturing sector companies in indonesia stockexchangefor 2009 and 2012 that has a complete annual report and the information can be accessedvia the internet, has a December 31 fiscal year and not delisting during the period of analysis. Theanalysis method in this study using statistical inferen parametric test with independent-sample t testand paired sample t test.The results with qualitative method, the independent sample t test, and with the pairedsample t test produces the same value of p valueis 0.000. Means the level of disclosure required(mandatory disclosure and voluntary disclosure) annual report are higherafter the implementation ofPSAK based on IFRS.